Innovative activity of industry under global crisis - Бондар-Підгурська, Оксана Василівна (Technology audit and production reserves, 2013)
Purpose. Based on the selection of the main criteria for the differentiation of crisis situations to develop a mechanism for their deployment at the micro and macro levels, and consider innovative activity of industry as a tool for renewal and economic development in the global crisis. Methodology. Methodological basis of study is general scientific research methods: methods of scientific analysis and synthesis, including systematic and logical analysis of the impact of innovation industry as a tool for renewal and economic development, and theoretical and methodological foundations of the system and process approaches also. As sources of information works of foreign and domestic scientists have been used. Findings. The necessity of intensification of innovation industry as a tool for renewal and economic development at all levels of administration; the conceptual framework of the national anticrisis of national industry was improved; the criteria of differentiation of crisis situations was systematized and developed for the first time; mechanism of crises deployment at the micro and macro levels of national industry was formed. Originality. The necessity of applying innovative activity as a tool for renewal and economic development in order to prevent and eliminate the consequences of adverse situations was proved and the criteria for the differentiation of crisis situations was elaborated, also a mechanism for deploying crises at the macro and micro levels of government was formed. Practical value. The results of research were implemented during teaching subjects "Situational management" and "Anticrisis Management" Higher Educational Institution of Ukoopspilka “Poltava University of Economics and Trade”